Fasciola hepatica products induce apoptosis of peritoneal macrophages - Guasconi, Lorena (2012)
Immunomodulatory properties have been described for Fasciola hepatica excretory-secretory products (FhESP), with their interaction with the innate immune cells being crucial during the early stages of infection. Previously, we demonstrated that FhESP induce eosinophil apoptosis. In this work, the ability of FhESP to induce apoptosis of peritoneal macrophages was evaluated.These parasite products were observed to induce apoptosis in peritoneal macrophages stimulated in vitro with FhESP, as well as in cells recovered from infected mice. The ability of FhESP to modify the viability of macrophages by apoptosis induction may constitute a crucial event for extending its survival in the host. © 2012 Elsevier B.V.